(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The influence of human resource accounting (HRA) on the decision-making process in abusiness with regards to both strategic and HR matters. During the course of this study, aninvestigation on the impact that HRA has on strategic HR decisions was carried out. The impact may beevaluated by looking at the various questions that were asked on the recruitment budget, attritioncontrol, performance management strategies, and the choice of training course. The HRA data that wasretrieved from the secondary sources was treated as if it were already known, which is a limitation ofthe research.